Analisis Sistem Pakar Diagnosa Penyakit THT Menggunakan Metode Certainty Factor - Dede Supriyadi; Farhan Rahmadi Fajar; Mellyana Utami; Siti Nurjanah; Astika Restiani; Yolen Perdana Sari; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
There are two factors and causes of a disease, namely Congenital and Acquired. Congenital is a disease that is congenital from birth and Acquired is a disease that is acquired after birth (diseases that are not congenital) such as infection, trauma, neoplasm (malignancy/tumor). Patients sometimes need information about the disease they are experiencing before deciding to go to a doctor or hospital. This information can be obtained through a system that can receive input in the form of symptoms of the disease and provide clear information about the disease. This can be done using an expert system, in this case the expert is an ENT (Ear, Nose, and Throat) specialist. The information is expected to have a solution for the illness. This ENT disease expert system designed and researched uses the certainty factor method. This method can overcome uncertainty in making decisions based on symptoms that are felt or inputted by the user. This research has successfully and precisely applied the certainty factor method as a decision-making tool in an ENT disease expert system. This system is web-based, so users can easily access and choose the symptoms they feel and find information about ENT diseases.